Potassium and risk of Type 2 diabetes. Issue 5 (September 2011) - Chatterjee, Ranee; Yeh, Hsin-Chieh; Edelman, David; Brancati, Frederick
The rising incidence and prevalence of Type 2 diabetes worldwide requires us to try to identify the determinants of this epidemic and to identify improved measures to prevent and treat this condition. While obesity is a major risk factor for diabetes, there are other risk factors that could potentially be corrected more easily. Potassium, both serum levels and to a lesser extent dietary intake levels, has been associated with incident diabetes. Lower levels of potassium have been found to be associated with a higher risk of diabetes in some studies. This article will review the literature available describing these associations and will help to identify where further research is needed.